Aspectos morfofisiológicos associados ao equilíbrio térmico de ovelhas da raça Morada Nova - Leite, Jacinara Hody Gurgel Morais (Universidade Federal Rural do Semi-Árido, 2016)
The Morada Nova sheep is an important locally adapted genetic resource from the Brazilian Semiarid. However, the genetic variability of these animals has been reduced due to the selection criteria adopted by breeders who only select to breed traits. One of these criteria is related to coat color, where the animals of red variety with dark and light tonality are discarded, as well as all animals of the white variety, with the justification that they are less adapted to the semiarid environment. Thus, in the present thesis was built in order to evaluate all characteristics related to the adaptation of Morada Nova sheep with different hair and coat color. Four groups were used according to coat color: (1) dark red animals, (2) intermediate red, (3) light red, and (4) white-coated animals. Forty Morada Nova ewes were observed in each of three herds for 7 consecutive months. In the first study we evaluated the thermal exchanges of sensible and latent heat loss in the different groups. All groups maintained homeothermy even when exposed to high solar radiation. The red coat animals increased respiratory rate in conditions of greater thermal stress. This fact was not observed in the white variety, which showed higher skin evaporation. In the second study, were evaluated hair coat characteristics and their association in the heat transfer from animals to the environment as well as physiological responses of animals. The largest differences found in the coat characteristics were recorded between the extremes of coat color: dark red and white. The white variety exhibited characteristics that promoted the protection of the skin, while red variety had characteristics which favored heat dissipation. It was concluded that Morada Nova sheep have good adaptability to the Semiarid environment, regardless of the coat color, and should be used in farming systems, preserved and multiplied
Morphophysiological characteristics associated with the thermal equilibrium of Morada Nova sheep
Keywords: Adaptação; Ambiente semiárido; Característica de pelame; Mecanismo latente; Adaptation; Coat traits; Thermal equilibrium; Semiarid region; CIENCIAS AGRARIAS::MEDICINA VETERINARIA